2023
DOI: 10.18632/aging.204277
|View full text |Cite
|
Sign up to set email alerts
|

miR-6742-5p regulates the invasion and migration of lung adenocarcinoma cells via mediating FGF8/ERK12/MMP9/MMP2 signaling pathway

Abstract: Background: microRNAs (miRNAs) are involved in the progression of Lung adenocarcinoma (LUAD), however, the functions of miR-6742-5p in LUAD remains unknown, thereby this study was carried on. Methods: The mRNA and miRNA expression data from the LUAD and normal control were obtained from Gene Expression Omnibus (GEO) database, TargetScan and mirDIP were applied to predict the relationship between miR-6742-5p and FGF8.Q-PCR, western blot, dual-luciferase, wound Healing and transwell assays were performed to test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 42 publications
(45 reference statements)
0
1
0
Order By: Relevance
“…In our study, we examined the expression of pSTAT1, a molecule expressed in macrophages to respond to lymphocytes. Previous studies have demonstrated the contribution of gelatinase MMP-2 and MMP-9 in cell migration [ 21 ], and we explored the role of MMP-9 in macrophage recruitment in GA and sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we examined the expression of pSTAT1, a molecule expressed in macrophages to respond to lymphocytes. Previous studies have demonstrated the contribution of gelatinase MMP-2 and MMP-9 in cell migration [ 21 ], and we explored the role of MMP-9 in macrophage recruitment in GA and sarcoidosis.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-6742-5p, miR-363-3p, miR-451 and miR-1258 are expressed at low levels in LUAD and inhibit cell proliferation. Mechanistically, they reduced the phosphorylation of the ERK1/2 protein through the ERK pathway, which is considered a classic branch of the MAPK signaling pathway (127,145,152,157). By contrast, miR-1307-5p and miR-25 participated in the regulation of LUAD as oncogenes through the ERK signaling pathway (127,159).…”
Section: Mirna-mediated Targeting Of Specific Signaling Pathways In Luadmentioning
confidence: 99%